Perfecting Plural Societies: Lessons from the Comparative Study of Property Systems and Jural Disparity in Two Philippine Ethnic Minorities - Wiber, Melanie G.; Prill-Brett, June (Culture, 1988)
Most nation states today are plural societies, with more than one tradition of economic, political and jural organization. As developing nations move towards increasing integration of peripheral regions and groups, the problems inherent in this plurality are becoming increasingly intractable. One significant problem area lies in rural development which involves land tenure and the western perception of “peasant” or tribal peoples as “common potatoes in a sack.” This paper compares the diachronic development of property systems in two neighbouring ethnic groups of upland northern Philippines to argue that more research is needed into the social processes resulting from plural jural institutions. Not all peripheral groups respond in the same ways to plural jural systems; the reasons for differing responses may tell us much about the phenomenon of growing inequality in developing nations.